Operative arthroscopy. - Johnson, Donald (Donald Hugh) (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
"Arthroscopy has become the major tool for orthopaedic surgeons fixing ligament problems in almost every anatomic joint in the human body. Chapter format to focus on how-to-do-it material The anatomic areas now covered are those that the sports medicine specialist will typically handle"--Provided by publisher.